Designing routine health check-ups for adolescents in Zimbabwe - Chingono, Rudo M (J Adolesc Health, 2021)
PURPOSE: The absence of routine health check-ups during adolescence in low- and middle-income countries is a missed opportunity for prevention, early identification, and treatment of health issues, and health promotion. We aimed to co-design the content and delivery for routine adolescent health check-ups in Zimbabwe, with adolescents and key adults in their lives. METHODS: We held participatory workshops with adolescents (16 workshops; 96 adolescents) and parents (8 workshops; 95 parents), and in-depth interviews with key informants including policy makers, programmers and healthcare workers (n=25). Analysis was iterative and the design of the check-ups was refined based on participant preferences, document review of burden of disease data, and feasibility considerations. RESULTS: Participants overwhelming supported the introduction of routine health check-ups. Reported facilitators to attendance included free cost and desire to know one’s health status. Barriers included tendencies for health service-seeking only when ill, fear of diagnosis and judgement, and religious beliefs. Delivery preferences were by non-judgemental medical professionals, in a youth-friendly environment, and accompanied by youth engagement activities. Preferred location was schools for younger adolescents (10-14 years), and community settings for older adolescents (15-19 years). Prioritised content included sexual health, oral health, mental health,hearing, eyesight, growth and nutrition, anaemia, immunisation, and deworming, based on health burden and participant preferences. DISCUSSION: This study resulted in an outline design of two routine health check-ups with stakeholders in Zimbabwe, in schools for young adolescents and in community settings for older adolescents. Evidence of feasibility, effectiveness and cost-effectiveness of such check-ups is required.